2023
DOI: 10.3389/fmicb.2022.1099502
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus and Vibrio vulnificus in vitro colonization on plastics influenced by temperature and strain variability

Abstract: Marine bacteria often exist in biofilms as communities attached to surfaces, like plastic. Growing concerns exist regarding marine plastics acting as potential vectors of pathogenic Vibrio, especially in a changing climate. It has been generalized that Vibrio vulnificus and Vibrio parahaemolyticus often attach to plastic surfaces. Different strains of these Vibrios exist having different growth and biofilm-forming properties. This study evaluated how temperature and strain variability affect V. parahaemolyticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 125 publications
1
7
0
Order By: Relevance
“…Due to multiple experimental conditions, it is difficult to reach a consensus on the effect of temperature on the formation of V. parahaemolyticus biofilms. Castro-Rosas and Escartin (2002) and Han et al (2016) agreed that the formation of V. parahaemolyticus biofilms on abiotic (stainless steel) and biotic surfaces (crustaceans and shrimp) is favored by temperatures above 30 • C. However, Leighton et al (2022) showed a greater biomass of V. parahaemolyticus biofilms cultured on glass and plastic at 25 • C compared to those cultured at 30 and 35 • C. Using the crystal violet microplate assay, Song et al (2017) also noted greater biofilm formation at 25 • C relative to 15 or 37 • C for a collection of both pathogenic and nonpathogenic V. parahaemolyticus strains. They also reported that, as a group, the pathogenic strains produced more biofilm at all temperatures.…”
Section: Factors Enhancing Biofilm Formation and Contaminationmentioning
confidence: 80%
See 3 more Smart Citations
“…Due to multiple experimental conditions, it is difficult to reach a consensus on the effect of temperature on the formation of V. parahaemolyticus biofilms. Castro-Rosas and Escartin (2002) and Han et al (2016) agreed that the formation of V. parahaemolyticus biofilms on abiotic (stainless steel) and biotic surfaces (crustaceans and shrimp) is favored by temperatures above 30 • C. However, Leighton et al (2022) showed a greater biomass of V. parahaemolyticus biofilms cultured on glass and plastic at 25 • C compared to those cultured at 30 and 35 • C. Using the crystal violet microplate assay, Song et al (2017) also noted greater biofilm formation at 25 • C relative to 15 or 37 • C for a collection of both pathogenic and nonpathogenic V. parahaemolyticus strains. They also reported that, as a group, the pathogenic strains produced more biofilm at all temperatures.…”
Section: Factors Enhancing Biofilm Formation and Contaminationmentioning
confidence: 80%
“…However, Leighton et al. (2022) showed a greater biomass of V. parahaemolyticus biofilms cultured on glass and plastic at 25°C compared to those cultured at 30 and 35°C. Using the crystal violet microplate assay, Song et al.…”
Section: Contamination Routes Of Processed Seafoodmentioning
confidence: 98%
See 2 more Smart Citations
“…Biofilm formation experiments on MPs were adapted from O'Toole (2011) , Hamanaka et al (2012) , Valquier-Flynn et al (2017) , and Leighton et al (2023) . In summary, MPs were generated from slide coupons of low-density polyethylene (LDPE), polypropylene (PP), and polystyrene (PS) ( Table 3 , Biosurface Technologies, Boseman, MT, United States) by cutting the coupons to dimensions of 4 mm x 1 mm.…”
Section: Methodsmentioning
confidence: 99%